2008
DOI: 10.1186/1751-0147-50-4
|View full text |Cite
|
Sign up to set email alerts
|

Managerial and environmental determinants of clinical mastitis in Danish dairy herds

Abstract: Background: Several management and environmental factors are known as contributory causes of clinical mastitis in dairy herd. The study objectives were to describe the structure of herdspecific mastitis management and environmental factors and to assess the relevance of these herdspecific indicators to mastitis incidence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
3
8
1
Order By: Relevance
“…We used factor loadings of 0.40 as a lower limit for a clinical variable to load on a given factor. A similar limit has been recommended by Sharma (1996), while another study reported a lower limit (0.30; Sato et al, 2008) and yet another study reported a higher limit (0.50; Thoefner et al, 2001). Having used a higher limit of the factor loadings in this study would not have changed the interpretation of the factors, since the clinical signs, which were important in the interpretation, had loadings above 0.5.…”
Section: Discussionsupporting
confidence: 75%
“…We used factor loadings of 0.40 as a lower limit for a clinical variable to load on a given factor. A similar limit has been recommended by Sharma (1996), while another study reported a lower limit (0.30; Sato et al, 2008) and yet another study reported a higher limit (0.50; Thoefner et al, 2001). Having used a higher limit of the factor loadings in this study would not have changed the interpretation of the factors, since the clinical signs, which were important in the interpretation, had loadings above 0.5.…”
Section: Discussionsupporting
confidence: 75%
“…The sum of these reports confirm that despite the use of sand in freestalls, the effect of housing and bedding on the incidence of intramammary infections and BTSCC is multifactorial and difficult to fully explain with survey studies without knowledge of application of management practices among farms. Several measures of attitudes and values were associated with BTSCC in this study, consistent with studies finding that attitudes of farm managers and owners about mastitis and milk quality may affect SCC, mastitis incidence, and use of antimicrobial agents (Bigras-Poulin et al, 1985;Barkema et al, 1999;Vaarst et al, 2002;Barnouin et al, 2004;Sato et al, 2008). In our study, respondents that scored higher on the mastitis problems attitude scale-belief that mastitis was a problem on their farm and that not following milking and treatment protocols was a problem-reported higher BTSCC.…”
supporting
confidence: 89%
“…Questions covered 7 categories: (1) sociodemographics and farm characteristics (age, education, race, Mennonite or Amish, native English speaking, herd size, and so on; Norman et al, 2011); (2) milking proficiency (pre-and postmilking teat disinfection, wearing gloves during milking, and so on; Erskine et al, 1987;Wenz et al, 2007); (3) milking systems (parlor type, maintenance patterns, and so on; Mein, 2012); (4) cow environment (housing, grouping, bedding, and so on; Dufour et al, 2011); (5) infected cow monitoring and treatment (record keeping, use of cultures, and so on; Wenz et al, 2007;Bhutto et al, 2011); (6) farm labor (number of workers, employee management strategies, and so on ;Fuhrmann, 2002;Brasier et al, 2006;Stup et al, 2006); and (7) attitudes toward mastitis and related antimicrobial agent use (farm goals, belief in causes of mastitis, sources of information about mastitis and antimicrobials, and so on, Vaarst et al, 2002;Wenz et al, 2007;Sato et al, 2008;Jansen et al, 2009).…”
Section: Survey Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…In the Nordic countries, mastitis incidence rates per lactation vary between 0.2 and 0.4 (Heringstad et al, 2000). Sato et al (2008) reported a mean rate of 44.7 cases per 100 cow-years for CM in Danish dairy herds.…”
Section: Discussionmentioning
confidence: 99%